The Analysis of Modal Hedges Used by the Main Character of the Comic Big Nate from the Top - Nibrosiyah, Zakiyatun (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper focuses on analyzing the modal hedges used on the main character of the comic Big Nate from the Top by Lincoln Peirce. The data of this study were taken by using the documentation method and note-taking technique from the comic Big Nate from the Top by Lincoln Pierce in 2010. This comic is an American daily comic strip beginning in 1991. Based on the background, the research about analyzing modal hedges used on the main character of the comic Big Nate from the Top by Lincoln Pierce was conducted on the following problem: First, What are the modal hedges used by the main character of the comic Big Nate from the Top by Lincoln Pierce? Second, how are the modal hedges used by the main character of the comic Big Nate from the Top by Lincoln Pierce? This study used the descriptive qualitative method. Thus, the data were obtained from the utterance of used the main character of the comic Big Nate from the Top by Lincoln Pierce. Data analysis exposed several findings answering the formulated research questions.